Renewable Energy Sources in the Baltic States and New Business Approach of the Sector - Viskuba, Karina; Silinevicha, Veronica (Vilnius University Open Series, 2021)
Renewable energy sources (RES) are efficient in meeting the demand for clean and affordable energy. The need for RES is undeniable and has many advantages but there are also some challenges that need to be taken into consideration and adapted to the energy system. One of the challenges is RES volatility and its impact on electricity prices and power system operation. Europe is trending to power system decentralisation through the involvement of local authorities, active consumers and citizens in the system operation. This article provides main information about the energy sector of Latvia and RES in the Baltic countries. It proposes a methodology for the complex analysis of correlation and regression dependences of natural and price indicators of the electric power industry, based on the adaptation of the corresponding classical mathematical models.